Evaluation of the international customs interaction effectiveness by the mirror comparison method of statistical data on foreign trade - A. A. Lisitsa (Управление, 2023)
Most of the strategic directions for improving customs administration in the Russian Federation, due to their specifics, involve interaction with the customs authorities of foreign states. The article discusses approaches to assessing the effectiveness of interstate customs interaction as a sub-type of the Russian customs service activity. The urgency of the problem lies in the fact that the basis of interstate customs interaction is the principle of minimizing possible customs risks. At the same time, the existing system of indicators used to evaluate the activities of customs authorities does not reflect the effectiveness of interaction in terms of the administration of these risks. The purpose of the study is to consider a process approach to assessing the effectiveness of customs cooperation in the concept of supply chain management. This approach involves an analysis of the activities of not a separate national customs administration, but an assessment of the integration of the actions of states in the context of concluded agreements on cooperation in the field of customs. A cross-border supply chain, according to the author, can have varying degrees of efficiency depending on the type of behavior of national customs administrations within it. The task of the study is to analyze the indicators of Russian and Chinese customs statistics of mutual trade by comparing “mirror” data on export-import transactions, extrapolating the trend of discrepancies to the dynamics of the development of customs cooperation between Russia and China, identifying elements that affect the gaps in mirror data. The results obtained suggest that, given a fairly definite and stable list of reasons for the discrepancies in the data of “mirror” customs statistics, their composition and degree of impact are different in each period of time and are a reflection of the level of interaction between the customs administrations of Russia and China. To verify the proposed approach, the trend of deviations of regional “mirror” statistics of bilateral trade between China and Russia is analyzed in the context of the cooperation key projects development between the Russian Far East and China customs administrations.